2012
DOI: 10.1371/journal.pntd.0001512
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mutations in Heterogeneous Miltefosine-Resistant Leishmania major Population as Determined by Whole Genome Sequencing

Abstract: BackgroundMiltefosine (MF) is the first oral compound used in the chemotherapy against leishmaniasis. Since the mechanism of action of this drug and the targets of MF in Leishmania are unclear, we generated in a step-by-step manner Leishmania major promastigote mutants highly resistant to MF. Two of the mutants were submitted to a short-read whole genome sequencing for identifying potential genes associated with MF resistance.Methods/Principal FindingsAnalysis of the genome assemblies revealed several independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 61 publications
8
93
2
4
Order By: Relevance
“…Although overexpression of these proteins leads to a gain-offunction resistance phenotype, Cos-Seq does not lend itself to isolation of loss-of-function transporter mutations, such as for the MTF transporter MT (10). Additional technical limitations associated with Cos-Seq include the failure to detect nonprotein drug targets or selection against specific regions whose overexpression would be toxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although overexpression of these proteins leads to a gain-offunction resistance phenotype, Cos-Seq does not lend itself to isolation of loss-of-function transporter mutations, such as for the MTF transporter MT (10). Additional technical limitations associated with Cos-Seq include the failure to detect nonprotein drug targets or selection against specific regions whose overexpression would be toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Eight cosmids were individually isolated for characterization, seven of which imparted MTF resistance between 1.7-and 3.2-fold (Table 1). MTF resistance is an easily selected phenotype as a result of single-point mutations in the MTF transporter (MT) (10,21). The latter is a loss-of-function event that would not be selected in the current screen.…”
Section: High-throughput Screening Of the Five Major Antileishmanial mentioning
confidence: 99%
“…For example, whole-genome sequencing was used to study experimental HePC resistance in L. major (43), and distinct mutations were identified, with a potential role in the mechanism of resistance. NGS also encompasses the study of the entire transcriptome of an organism via RNA-seq, with the advantage of quantifying the most significant changes in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sequencing of the genome of miltefosine-resistant mutants pinpointed a mutation in the pyridoxal kinase (PLK) gene (Fig. 4e), and the role of this gene in MIL resistance was confirmed by gene transfection experiments (Coelho et al 2012). …”
Section: Miltefosinementioning
confidence: 96%
“…Interestingly, the resistance phenotype seems stable in in vitro macrophages infected with MT-null mutant and MT-mutated parasites (Seifert et al 2007), suggesting that what is observed in MIL-resistant promastigotes might be applied to intracellular amastigotes. Moreover, several mutations in MT can lead to resistance, and within a resistant population, they may be several different MT genotypes, leading to resistance (Coelho et al 2012).…”
Section: Miltefosinementioning
confidence: 99%